2021
DOI: 10.1097/mao.0000000000003178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spin in the Abstracts of Systematic Reviews and Meta-Analyses Focused on Tinnitus

Abstract: Hypothesis:The objective was to investigate the prevalence of spin in abstracts of systematic reviews and meta-analyses covering the treatment of tinnitus. We hypothesized that spin would be present in these articles and a significant relationship would exist between spin usage and extracted study characteristics. Background: Spin, the misrepresentation of study findings, can alter a clinician's interpretation of a study's results, potentially affecting patient care. Previous work demonstrates that spin is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
3
6
0
Order By: Relevance
“…33 However, percentages of abstracts containing spin from other medical specialties and disorders were similar to that of ours: smoking cessation (3.5%), 34 ophthalmology (2.9%), 35 and otolaryngology (10%). 36 While our findings showed lower amounts of spin compared to systematic reviews in other fields, the most common spin types were similar to the findings of Ottwell and colleagues who also found the two most prevalent spin types to be types three and five. 32 While our findings showed lower amounts of spin occur compared to most other fields, the most common spin types were similar to the findings of Ottwell and colleagues who also found that spin types three (Selective reporting of or overemphasis on efficacy outcomes or analysis favouring the beneficial effect of the experimental intervention) and five (Conclusion claims the beneficial effect of the experimental treatment despite high risk of bias in primary studies) occurred frequently.…”
Section: Primary Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…33 However, percentages of abstracts containing spin from other medical specialties and disorders were similar to that of ours: smoking cessation (3.5%), 34 ophthalmology (2.9%), 35 and otolaryngology (10%). 36 While our findings showed lower amounts of spin compared to systematic reviews in other fields, the most common spin types were similar to the findings of Ottwell and colleagues who also found the two most prevalent spin types to be types three and five. 32 While our findings showed lower amounts of spin occur compared to most other fields, the most common spin types were similar to the findings of Ottwell and colleagues who also found that spin types three (Selective reporting of or overemphasis on efficacy outcomes or analysis favouring the beneficial effect of the experimental intervention) and five (Conclusion claims the beneficial effect of the experimental treatment despite high risk of bias in primary studies) occurred frequently.…”
Section: Primary Findingssupporting
confidence: 89%
“…Similarly, Reddy et al found that 36% of systematic reviews on rotator cuff management contained spin in their abstract 33 . However, percentages of abstracts containing spin from other medical specialties and disorders were similar to that of ours: smoking cessation (3.5%), 34 ophthalmology (2.9%), 35 and otolaryngology (10%) 36 32 …”
Section: Discussionsupporting
confidence: 76%
“…Our team's previous investigations found spin in abstracts at rates ranging from 37% in oncology RCTs [18] to 70% in otolaryngology RCTs [37]. More recently, studies have shown that spin frequently occurs in abstracts of systematic reviews [38][39][40][41][42][43][44][45][46][47][48]. As previously mentioned, Ottwell et al [20] identified spin in 31% of the included abstracts of systematic reviews and meta-analyses on acne vulgaris therapies, a finding similar to ours.…”
Section: Xsl • Fosupporting
confidence: 86%
“…al found that 37.5% of SRs in regards to the treatment of tinnitus was critically low and only 12.5% were of high quality. 53 Moreover, Martinez-Mondero et al concluded that "over 50% of these SRs and MAs had weaknesses in at least 3 of the 16 items in the AMSTAR-2." 54 Taken together, our findings are consistent with the existing literature across multiple disease processes within otolaryngology and other medical specialties.…”
Section: Discussionmentioning
confidence: 99%